THE EFFECT OF COVID 19 ON COMPANY PERFORMANCE IN MANUFACTURING COMPANIES IN INDONESIA - Retno Cahyaningati; Ninik Lukiana; M.Wimbo Wiyono; Kasno Kasno; Muhammad Rizalus Sholihin; Deni Juliasari (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study was conducted to determine and explore the effect of the COVID-19 pandemic on company performance using control variables for sales growth, leverage, and company size in companies listed on the Indonesia Stock Exchange Design/methodology/approach: The study used a population of manufacturing companies listed on the Indonesia Stock Exchange for the quarter/quarter period during 2020. The sample was taken using purposive sampling 148 observation companies matched the research criteria. This study uses secondary data, namely the quarterly/quarterly financial statements of each sample company Findings: The results showed that in testing the partial correlation of the independent variables, namely covid 19 with the control variables of sales growth, leverage and company size has a significant effect on company performance, but the effect was still weak. Partially covid 19 has a significant positive effect on company performance. Partially, sales growth has no significant effect on the company's performance. Partially, leverage has no significant effect on company performance. Partially, company size has a significant positive effect on company performance. Simultaneously, the independent variables of covid 19, sales growth, leverage, and company size significantly affect the performance of manufacturing companies listed on the Indonesia Stock Exchange in 2020. Research limitations/implications: Implikasi teoritis dalam penelitian ini berfokus pada tingkat kinerja perusahaan, Penelitian kami membahas secara konprehensif pengaruh pandemi Covid 19 terhadap kinerja perusahaan. Practical implications: Untuk pelaku bisnis di ASIA diharapkan dapat menemukan solusi terkait adanya ketidakpastian global ini Originality/value: Covid 19 ke kinerja perusahaan dengan pertumbuhan penjualan, leverage, size sebagai variabel kontrol. Paper type: Research paper Keyword: Covid 19, sales growth, leverage, company size, and firm performance.